(untitled) (Research, Society and Development, 2020)
The cell phone is a technological resource widely used today, whether for children, young people or adults. Just as it is important for this public on a daily basis, the cell phone is also an important resource for eeducation. However, this utility is also still questionable with regard to the benefits achieved with this practice in the classroom. There are many discussions about the use of this electronic device as a useful tool for teaching-learning practices. From this perspective, our objective in this work is to map the academic productions located in the repository of the Theses and Dissertation Capes catalog that discuss the use of cell phones as a didactic resource in the classroom. For that, we opted for the type of research State of knowledge that is characterized by the survey, selection and analysis of data in only one database. As proceeded, a quantitative of 27 works was obtained and after refinement made from some descriptors, 11 publications were selected, which made up the corpus of this study. In summary, the results reveal that the greatest interest of researchers is concentrated in the use of cell phones as a didactic resource in the scope of exact sciences and natural sciences, with emphasis on the subjects of Mathematics and Physics which together add up to a greater number of published productions. Therefore, the results also reveal an increase in the number of researches on the topic under study.